(3CQLhRI ddEeGe Ydj QVj Gddg Yfgs - (3GdgGTej, GdbQTj, CHh GdMSf, Ydj Hf CHj WGdH Hf YHO GdeWdH, J (B40 (3gs
(3ChdgG (B:s
(3GdMeO ddg GdYdj GdUGOb (B*** (3GdhGMO Gdbhj GdYdje GdQGRb , Gdedc GdbOhS Ph GdLdGd (B*** (3ebOQ GdCQRGb hGdBLGds
(3BNQgG (B:s
(3Ke cdGe Ve Vef QLRg (B*** (3LhGgQ bO CNQLJ ef cfRg , aGdYde ddg HeG jLOjg (B*** (3hGdMeO ddg HeG CWhjgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 295s
(3eYLe GdeDdajf(B: 2 / 452s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs